FAKTOR YANG MEMPENGARUHI PENGGUNAAN E-MONEY: STUDI PADA MAHASISWA UNIVERSITAS TARUMANAGARA - Keegan, Kevin Kusuma; Lukman, Hendro; Simina, Juni (Jurnal Paradigma Akuntansi, 2025)
The era of the industrial revolution had an impact on economic activities for the community to switch to a digital-based economy. As well as providing ease of economic activity for the community. One of them is the transition from cash to e-money. In its use e-money is influenced by factors of trust, security, convenience which is the intention of this research. The purpose of this study is to determine the effect of trust, security and convenience on the use of e-money. Subjects in this study were students. Samples were taken using simple random sampling method with a total of 80 students. Data processing techniques for descriptive analysis use the SPSS (Statistical Product and Service Solution) Application for Windows version 22.0 and Smart PLS Version 4.0. The results of this study indicate that trust has no significant effect on the use of e-money. and security have no significant effect on the use of e-money. Meanwhile, convenience has a significant effect on the use of e-money. The implication of this research is that if in this study a digital application for processing information which is easy to use, hassle- free, practical, will invite someones interest to use it.